Eine Geschichte mit Geschmack Die Natur synthetischer Aromastoffe im 20. Jahrhundert am Beispiel Vanillin - Gennermann, Paulina S. (De Gruyter, 2023)
It is difficult to imagine food today without flavorings, whether natural, synthetic, or artificial. But at the same time, they are substances that society is viewing increasingly critically and whose chemical and industrial roots are under scrutiny. A History with Taste tells the story of flavor production and regulation, discussing the potential naturalization of synthetic flavorings.